Comparação da composição bioquímica do líquido amniótico equino colhido em diferentes estágios gestacionais e no momento do parto - Vita, Bruna De [UNESP]; Campos, Loreta L. [UNESP]; Listoni, Amanda J. [UNESP]; Martin, Ian [UNESP]; Takahira, Regina Kiomi [UNESP]; Curcio, Bruna R.; Landim-alvarenga, Fernanda C. [UNESP]; Prestes, Nereu Carlos [UNESP] (Colégio Brasileiro de Patologia Animal - CBPA, 2014)
The viability and fetal maturity can be estimated by biochemical evaluation of the fetal fluids of several species; however the biochemical composition of amniotic fluid during pregnancy is not fully defined for equine. The aim of this study was to establish and compare the biochemical profile of amniotic fluid in different moments of pregnancy and at delivery, in order to better explain the peculiarities of the physiology of pregnancy in mares. The values founded for pH, osmolarity, glucose, urea, creatinine, gamma-GT, Sodium, potassium, chloride and total protein were evaluated in amniotic fluid collected from 122 mares comparing the results between the initial-third (IT), mid-third (MT) and latter-third (FT) of gestation and at delivery (D). The gestational period samples were collected at slaughterhouses. Gestational ages (IG), in days, were defined following the regression formula suggested by Naves et al. (2008) by measuring the craniocaudal (CC) distance of the fetuses. Commercial kits for biochemical evaluation were used. Due to the presence of varying degrees of asymmetry and deviations from a standard Gaussian distribution, the Kruskal-Wallis test was used to compare the median of each response variable among the study groups. When there has been significant evidence that at least one of the medians differed from the others, the Wilcoxon test was used to perform multiple comparisons between groups. The Bonferroni method was used to adjust the resulting p-value for multiple comparisons. Statistical analysis was performed using PROC Npar1way and statistical significance was defined as p<0.05. The pH and osmolarity of equine amniotic fluid did not change significantly during the stages of pregnancy and at delivery. The values found for glucose were significantly lower during late pregnancy and at delivery. Concentrations of urea tended to be statistically different in at least one of the groups. A significant increase in creatinine concentrations was observed during the initial-third, medium-third and the final-third of pregnancy and the value found at delivery remained equal to final-third. Values for Gamma GT differed only between FT and D groups and more studies should be conducted about its role in the amniotic fluid of domestic species. For the sodium and chloride ions, they were not significantly different between the studied stages, and the potassium ion was significantly different only between FT and D reflecting the maintenance of electrolyte balance of the amniotic fluid during equine pregnancy. Total protein concentrations were different between groups, but all the groups showed low concentrations. We conclude that the values of the parameters studied varied according with the fetal development and can be used for the evaluation of fetal viability and maturity in the future, but the scarce number of studies in this area and the difference between the results found in literature demonstrate the need of more works to establish the biochemical profile of equine amniotic fluid during pregnancy and at delivery.

A viabilidade e maturidade fetais podem ser estimadas através da avaliação dos fluídos fetais em muitas espécies, no entanto a composição bioquímica do líquido amniótico durante a gestação ainda não está bem definida para a espécie equina. O objetivo deste estudo foi estabelecer e comparar o perfil bioquímico do liquido amniótico em diferentes momentos da gestação e no momento do parto para um melhor entendimento da fisiologia da gestação de equinos. Foram avaliados valores encontrados para pH, osmolaridade, glicose, uréia, creatinina, gamma-GT, sódio, potássio, cloretos e proteína total no liquido amniótico colhido de 122 éguas comparando-se os resultados encontrados entre as colheitas em terço inicial (TI), médio (TM) e final (TF) da gestação e no momento do parto (MP). As amostras colhidas nos períodos gestacionais foram realizadas em frigoríficos abatedouros. As idades gestacionais (IG), em dias, foram definidas através de fórmula de regressão sugerida por Naves et al. (2008), utilizando-se a mensuração crânio-caudal dos fetos. Devido a presença de graus variados de assimetria e desvios de um padrão Gaussiano de distribuição, o teste de Kruskal-Wallis foi usado para comparar a mediana de cada variável-resposta entre os grupos de estudo. Quando houve evidência significante de que pelo menos uma das medianas era diferente das outras, o teste de Wilcoxon foi usado para realizar comparações múltiplas entre os grupos. O método de Bonferroni foi usado para ajustar o valor-P resultante das comparações múltiplas. A análise estatística foi realizada com o procedimento PROC NPAR1WAY e significância estatística foi definida como p<0,05 .pH e osmolaridade do líquido amniótico equino não sofreram alterações significantes entre os terços gestacionais e no momento do parto. Os valores encontrados para glicose foram significativamente menores nas amostras do grupo TF e MP. As concentrações de uréia tenderam ser estatisticamente diferente em pelo menos um dos grupos estudados e foi observado um padrão crescente nas concentrações de creatinina durante as fases gestacionais, enquanto que a concentração encontrada no grupo MP foi igual a concentração encontrada no grupo TF. Valores para gamma GT diferiram apenas entre os grupos TF e MP e mais estudos devem ser conduzidos sobre sua função no liquido amniótico das espécies domésticas. Os valores de sódio e cloretos não diferiram significativamente entre os grupos estudados e as concentrações de potássio diferiram apenas entre os grupos TF e MP refletindo a manutenção do equilíbrio eletrolítico do líquido amniótico equino durante a gestação. As concentrações de proteínas totais variaram de maneira heterogênea entre os grupos, porém todos estes demonstraram baixas concentrações. Concluímos que a composição bioquímica do liquido amniótico equino varia de acordo com o desenvolvimento fetal e pode ser utilizada como mensuração da viabilidade e maturidade do feto no futuro, no entanto devido ao pequeno número de estudos conduzidos e diferenças encontradas em seus resultados, outros estudos devem ser realizados para a melhor definição do perfil bioquímico do líquido amniótico equino durante as fases gestacionais e no momento do parto.
Comparison of the biochemical composition of equine amniotic fluid collected in different gestational phases and at delivery
Keywords: Equino; líquido amniótico; avaliação bioquímica; viabilidade fetal; Equine; amniotic fluid; biochemical evaluation; fetal viability